Septicaemia and meningitis caused by dysgonic fermenter-2 (DF-2). Issue 9 (September 1986) - Chan, P C; Fonseca, K
Abstract : A patient developed dysgonic fermenter-2 (DF-2) septicaemia and meningitis after having been bitten by a dog. The pathogenic organism was isolated from the oral cavity of the dog, which, it is believed, is the first time that this has been done. The growth characteristics of the organism and the immunological response of the patient were studied. The isolation of the infecting agent from the dog confirms that the oropharyngeal flora of dogs is a reservoir of the organism: the fastidiousness and slow growth of this Gram negative bacillus may account for the small number of reported cases of infection caused by this organism.